Luciogobius yubai, a new species of gobioid fish (Teleostei: Gobiidae) from Japan - Ikeda, Yuji; Tamada, Kazuaki; Hirashima, Kentarou (Zootaxa, 2019)
A new gobioid fish Luciogobius yubai sp. nov. is described based on specimens collected from Wakayama and Shizuoka Prefectures, Japan. This species is distinguished from congeners by the following combination of characters; second dorsal-fin I, 9, anal-fin I, 10, pectoral-fin 17 or 18, vertebrate number 16+19=35, the first space between anterior two pterygiophores of second dorsal-fin placed the neural spines of vertebrae 17–18 or 17, four to seven developed dermal flaps under the eye longitudinally, posterior part of eye ridge protruded posteriorly, pectoral-fin with a long uppermost free ray, eye diameter 7.3–10.6 % of head length, pectoral-fin length 14.4–16.9 % of standard length (SL) , second dorsal-fin length 9.7–11.8 % SL, anal-fin ray length 9.1–11.1 % SL, pelvic-fin length 7.3–10.8 % SL, head and body with brownish orange coloration when alive or fresh.